Pausing of golgi bodies on microtubules regulates secretion of cellulose synthase complexes in arabidopsis - Crowell, Elizabeth Faris; Schumacher, Karin (The plant cell, 2009)
Plant growth and organ formation depend on the oriented deposition of load-bearing cellulose microfibrils in the cell wall. Cellulose is synthesized by plasma membrane-bound complexes containing cellulose synthase proteins (CESAs). Here, we establish a role for the cytoskeleton in intracellular trafficking of cellulose synthase complexes (CSCs) through the in vivo study of the green fluorescent protein (GFP)-CESA3 fusion protein in Arabidopsis thaliana hypocotyls. GFP-CESA3 localizes to the plasma membrane, Golgi apparatus, a compartment identified by the VHA-a1 marker, and, surprisingly, a novel microtubule-associated cellulose synthase compartment (MASC) whose formation and movement depend on the dynamic cortical microtubule array. Osmotic stress or treatment with the cellulose synthesis inhibitor CGA 325'615 induces internalization of CSCs in MASCs, mimicking the intracellular distribution of CSCs in nongrowing cells. Our results indicate that cellulose synthesis is coordinated with growth status and regulated in part through CSC internalization. We find that CSC insertion in the plasma membrane is regulated by pauses of the Golgi apparatus along cortical microtubules. Our data support a model in which cortical microtubules not only guide the trajectories of CSCs in the plasma membrane, but also regulate the insertion and internalization of CSCs, thus allowing dynamic remodeling of CSC secretion during cell expansion and differentiation.